A CONTRIBUTION TO THE THEORY AND THE DEVELOPMENT OF REPAIRING GRAY CAST IRON COMPONENTS CONTAINING SURFACE DEFECT - SATYA PERMANA , MUKI
Repair of the gray cast iron component containing surface defect is often necessary in many industries. The well established methods for repairing that component are Flame Spray and Shielded Metal Arc Welding (SMAW). However, the gray cast iron is very difficult to repair by welding due to the formation of brittle white cast iron along with the occurrence of micro-cracks (fissures). Welding process is also consumes long exposure time at high temperature, leading to graphite coarsening and high residual stress near the repaired defect. The combination of white cast iron, fissures and other lacks mentioned above will lead to the failure on the component in the vicinity of the repaired defect. Many efforts have been made to use other methods which are Ultrasonic Insert Casting, Diffusion Bonding, and Impact-Electric Current Discharge Joining. Nevertheless, these methods have not been yielding a satisfying solution due to a relatively low repaired strength. They are also impractical, costly, and inapplicable for the large components having variation of defects dimensions and geometries. From the economic point of view, repair process will decrease production cost at a significant level. The repair cost much cheaper compared to the new imported component which is very expensive. Based on the industrial data, the components to be repaired are numerous. For example, one of the industries has 52 cylinder heads to be repaired during months of April and May 2004. Therefore, a study concerning the theory and the development of repairing gray cast iron containing surface defects should be performed to overcome the existing repair problem. The aim of this research is to develop know how in repairing gray cast iron to overcome the weaknesses of the well established welding processes. The target of the repaired know how is to get an excellent metallurgical bonding in the area of the repaired defect that is free of white cast iron. The development of new method is relied on the hypothesis that if the repair is performed by pouring the molten metal into the surface defects with high enough heat input to locally melt the surface, hence the joining will occur at controlled cooling rate in order to get white cast iron free structures. iii The approached in the problem solution is performed by experiments, dimensional analysis and numerical analysis based on computer solution. The experimental approach is focused on creating some ideas translated into the design alternatives (conceptualization). The next step is to examine the design alternatives to get a potential method to fulfill the objective criteria on this research. The numerical approach is aimed to simulate the physical phenomena during repair that occur on the area of the repaired defect and to yield a number of new data as complement to the experiment results. Dimensional analysis approach is used to build a mathematical formulation as a generalization of the new method. Four methods of repairing have been developed i.e. Pouring, Powder Filling, Droplet Spray and Turbulence Flow Casting (TFC). TFC method has been proven to the objective of this research. Joining occurs as a result of convection heat transfer of molten flow into the sand mold which melts the existing base metal inside the mold and subsequent solidification. The experiment results proved that the metallurgical bonding at the joint was excellent since the fracture location occur at the weld pool where the tensile strength was about 200 MPa. TFC method, as a new repair solution, is powerful since the joint area after repair process is free of cracks and brittleness. The utilization of TFC can minimize the cooling rate, preventing the formation of the undesirable white cast iron. Moreover, the homogeneity in properties at the area of repaired was back to the original characteristics or like new. Through the appropriate selection of parameters, TFC method can be able to repair defects without resulting in the presence of white cast iron, martensite, cracks and porosities. However, the parameters can only be applied to a certain defect dimension so that it has limited application. In order to overcome this limitation, determination of parameters is approached by the mathematical formulation representing generalization of TFC process. Therefore, the formulation can be applied to the various defect dimensions as long as it fulfills the similarity principle. In this work, the similarity principle is used for Reynolds and Prandtl numbers of 11,100 and 0.14 respectively and the similarity of geometry is in the form of cylindrical channel. Preheat to the component is a dominant factor repair process by TFC method. For the large component (more than 500 mm thick), the preheating may be done by stove, molten metal, heating coil or some other methods or even a combination of them all. Nevertheless, the main idea for successful repair in TFC is such that the preheating should provide a sufficient heat input to get a low cooling rate in the vicinity of the repaired defect. Mathematical Formulation resulted from the dimensional analysis approach can be related to the other material such as stainless steel and aluminum alloys. Repair method developed in this work represents a new breakthrough having contribution to the manufacturing technology. Therefore, it can be proposed to make standardization especially in repairing grey cast iron components containing surface defect